Cognitive change is more positively associated with an active lifestyle than with training interventions in older adults at risk of dementia: a controlled interventional clinical trial. Issue 1 (December 2016) - Küster, Olivia; Fissler, Patrick; Laptinskaya, Daria; Thurm, Franka; Scharpf, Andrea; Woll, Alexander; Kolassa, Stephan; Kramer, Arthur; Elbert, Thomas; von Arnim, Christine; Kolassa, Iris-Tatjana
Abstract Background While observational studies show that an active lifestyle including cognitive, physical, and social activities is associated with a reduced risk of cognitive decline and dementia, experimental evidence from corresponding training interventions is more inconsistent with less pronounced effects. The aim of this study was to evaluate and compare training- and lifestyle-related changes in cognition. This is the first study investigating these associations within the same time period and sample. Methods Fifty-four older adults at risk of dementia were assigned to 10 weeks of physical training, cognitive training, or a matched wait-list control condition. Lifestyle was operationalized as the variety of self-reported cognitive, physical, and social activities before study participation. Cognitive performance was assessed with an extensive test battery prior to and after the intervention period as well as at a 3-month follow-up. Composite cognition measures were obtained by means of a principal component analysis. Training- and lifestyle-related changes in cognition were analyzed using linear mixed effects models. The strength of their association was compared with pairedt -tests. Results Neither training intervention improved global cognition in comparison to the control group (p = .08). In contrast, self-reported lifestyle was positively associated with benefits in global cognition (p < .001) and specifically in memory (p < .001). Moreover, the association of an active lifestyle with cognitive change was significantly stronger than the benefits of the training interventions with respect to global cognition (p s < .001) and memory (p s < .001). Conclusions The associations of an active lifestyle with cognitive change over time in a dementia risk group were stronger than the effects of short-term, specific training interventions. An active lifestyle may differ from training interventions in dosage and variety of activities as well as intrinsic motivation and enjoyment. These factors might be crucial for designing novel interventions, which are more efficient than currently available training interventions. Trial registration ClinicalTrials.gov IdentifierNCT01061489 . Registered February 2, 2010.